Forest protection and air pollution control from open burning: application of prescribed burning under environmental law in Malaysia - Mustafa, Maizatun; Yaakob, Adzidah; Ariffin, Mariani; Mohd Rusli, Mohd Hazmi (2017)
There is a possible connection between the control of forest fire and open burning with the protection of air quality. In the case of Malaysia, activities relating to open burning have been identified to be among the contributors of air pollution and haze phenomenon that are causing a deteriorating quality of the atmosphere. However, a total prohibition on open burning may not be practicable in the context of Malaysia due to various factors including that concerning land-use practices. In this region, the land-use systems are relying on open burning as one of the methods of land clearing. Some agricultural and farming processes especially among the smallholders and subsistence farmers are still based on the traditional method of using fire. For the policy makers, these are factors that need to be taken into consideration when formulating a law on open burning in order to strike a balance between land-use management and environmental protection. For this reason, this paper seeks to highlight status of forest fires and open burning, and to examine the application of prescribed burning within environmental law in Malaysia which is considered a suitable tool for management practice in forest and other land-use policy. The paper argues that prescribed burning, if strictly performed, can help harmonise different interests and help accomplish the target of forest protection and air pollution control in accordance with acceptable legal parameters.